The Concept of Digital Asset Inheritance in the Perspective of Faraid Science (A Study of the Application of Blockchain-Based Crypto) - Santoso, Muhammad; Hasanudin, Fuat (Indonesian Journal of Law and Justice, 2026)
This normative legal research aims to analyze the legal standing of crypto assets in Islamic inheritance law and to formulate an adaptive faraid approach capable of addressing their non-custodial characteristics. The study employs qualitative doctrinal analysis using the methods of qiyas  (analogical reasoning) and maqashid sharia  (objectives of Islamic law) to examine the inheritance implications of crypto assets stored on blockchain systems. In the analytical process, locked digital assets are analogized to buried treasure  (rikaz) to establish their proprietary status, while reference to Law No. 4 of 2023 concerning the Financial Sector Development and Strengthening  (PPSK Law) is utilized to reinforce their legality as recognized inheritance objects within the national legal framework. The findings confirm that crypto assets can be validly categorized as māl mutaqawwim  (legally valuable property) because they fulfill the elements of hiyazah  (legitimate control) and intifa’  (beneficial use), thereby making them subject to inheritance distribution. However, their dependence on private keys presents significant technical barriers to execution and transfer. To address this issue, the study proposes the implementation of Wasiyyah al-Isya’  (testament of access) as a preventive mechanism aligned with the principle of hifz al-mal  (protection of wealth), ensuring heirs’ access to digital assets. Additionally, for indivisible or technically complex assets, the application of the at-takharuj (peaceful settlement) mechanism is recommended, whereby ownership is transferred to technologically competent heirs who provide equitable compensation  (iwadh) to other heirs. This adaptive framework ensures legal certainty, distributive justice, and alignment with the objectives of Sharia in the digital era.